2014
DOI: 10.2460/javma.244.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter prospective evaluation of dogs with trauma

Abstract: Results indicated ATT and MGCS scores were useful for prediction of outcome for dogs evaluated because of trauma. Penetrating trauma, low blood lactate concentration, and performance of surgical procedures were predictive of survival to hospital discharge. The methods enabled collection of data for a large number of dogs in a short time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
117
5
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(140 citation statements)
references
References 19 publications
16
117
5
2
Order By: Relevance
“…[10][11][12][13][14][15]21 The small numbers of cats in our study likely decreased our ability to detect a significant association between initial lactate concentration or lactate concentration change during hospitalization and outcome. In addition, for cats that had the measurement repeated during hospitalization, there was no association between an increase or decrease in lactate concentration and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15]21 The small numbers of cats in our study likely decreased our ability to detect a significant association between initial lactate concentration or lactate concentration change during hospitalization and outcome. In addition, for cats that had the measurement repeated during hospitalization, there was no association between an increase or decrease in lactate concentration and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh whole blood is the ideal fluid to replace blood loss, as it provides platelets, red blood cells, fibrinogen and clotting factors; however, this resource is rarely available in the emergency setting and packed red blood cells (PRBC) and fresh-frozen plasma (FFP) may represent a more realistic option, even though their availability remains limited in veterinary medicine (Fig 3). In veterinary practice, most of the cases with traumatic haemoabdomen will not require blood products at all (Hall and others 2014). …”
Section: Management Of the Most Common Emergency Injuriesmentioning
confidence: 99%
“…Penetrating injuries are usually a result of bite wounds in dogs (74 per cent of the total penetrating trauma in a retrospective study [Hall and others 2014]), with other causes including gunshots and stab wounds. As a general rule, when a trauma results in penetration of the abdomen an exploratory surgery should be planned to assess if there is any organ damage (Culp and Silverstein 2014) and to treat any contamination (either from the penetrating wound or due to organ damage).…”
Section: Penetrating Injury and Septic Peritonitismentioning
confidence: 99%
“…The MGCS total score ranges from 3 to 18, with the lowest score representing the worst neurological status and the lowest probability of survival within the first 48 hours after head trauma (Platt and others 2001). A recent single-centre retrospective study reported that up to 25 per cent of dogs with severe blunt trauma suffer from TBI (Hall and others 2014). …”
Section: Traumatic Brain Injurymentioning
confidence: 99%